The education–suicide mortality gradient. Issue 9 (21st May 2019) - Cook, Adam
ABSTRACT: Using the fifth release of the National Longitudinal Mortality Survey, I examine the role of educational attainment and self-reported health on 6- and 11-year suicide mortality risk in the United States. I first replicate the original results reported by Hamermesh and Soss. . Then, augmenting the Hamermesh model with initial educational attainment and self-reported health status, I find that years of education significantly raises suicide mortality risk in the US after controlling for initial self-reported health. This result is robust to regression specification, replication and the inclusion of covariates.